Development and Evaluation of Inclined Plate Metering Mechanism For Carrot (Daucus Carota L.) Pelleted Seeds - Gautam, Anand; khurana, Rohinish; Singh Manes, Gursahib; Dixit, Anoop Kumar; Verma, Aseem (International Journal of Bio-resource and Stress Management, 2019)
Carrot can be grown by direct seeding method which can help in saving labour. Small and irregular shaped seed lead to variation and placement of the seeds when sown using existing planters. Seed pelleting was done in the ratio of 1:1, 1:2 and 1:3 so that the physical properties of the seeds are altered to be applicable for use with an inclined plate planter. An inclined plate planter was developed for pelleted seeds. Preliminary evaluation of the developed planter was done in the laboratory for the treated seeds using different developed seed plates having 18, 24 and 30 grooves at forward speeds of 1.0, 2.0 and 3.0 km h-1 and inclination angle 40°, 45° and 50°. Performance was evaluated on the basis of average spacing, missing index, multiple index and quality of feed index. Average seed spacing obtained at in 1:3 seed, 45° angle in forward speed 2.0 km h-1, the average spacing was observed to be 4.48, 4.29 and 4.11 cm for 18, 24 and 30 groove plate respectively. Missing index at 2.0 km h-1 forward speed with 24 groove seed metering plate with 45o inclination angle was 5.0% and multiple index was 14.0%. The selection of plate inclination and type of metering cell for the planter was purely based on average spacing, missing index, multiple index and quality of feed index. With 24 groove seed metering plate with 45o inclination angle and forward speed of 2.0 km h-1 was selected for the field evaluation.